Keabsahan Akta Jual Beli Saham Perseroan Terbatas yang Belum Memperoleh Status Badan Hukum - Mochamad Cholil; Deni Santi Pertiwi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study examines the validity of share purchase and sale agreements in limited liability companies that have not yet obtained legal entity status. The issue arises because shares, as objects of corporate law, only come into existence after the company is registered with the Minister of Law and Human Rights and obtains proof of registration in accordance with Article 7(4) of the Limited Liability Companies Act, as amended by the Job Creation Law. The results of the discussion indicate that a share purchase and sale agreement entered into before the company obtains legal entity status does not yet result in a legal transfer of rights to the shares, but rather constitutes only an obligatory relationship between the parties. Therefore, legal protection must be ensured through legal certainty and the application of the principle of prudence.